Los materiales del método Montessori y el proceso de enseñanza y aprendizaje de la lectoescritura en un estudiante de quinto grado de la Unidad Educativa Fiscomisional Educare. Periodo 2023. - León Gálvez, Rut Patricia (2023)
The objective of this study was to contribute to the improvement of the teaching and learning process of reading and writing through the use of Montessori method materials, applied to a fifth grade student at Phisyocomisional Educational Unit Educare. Thus, a qualitative approach research related to the case study was carried out. The data collection instruments were a psycho-pedagogical sheet, a semi-structured interview with the teachers and the T.A.L.E test. to evaluate the student's reading and writing characteristics. The before and after methodology was used, in such a way that prior to the proposal the results indicated that the student has a profile with a reading-writing level below that corresponding to his age. In this sense, a psychopedagogical proposal was designed and applied based on the use of Montessori material to promote learning; The progress obtained was evidenced through achievement sheets and the learning achievements after the application of the proposal were evaluated using a checklist. Finally, it was concluded that the psychopedagogical proposal based on the use of Montessori material generated a positive impact on the teaching and learning process of literacy and developed in the student the ability to read and write. Keywords: Montessori materials, teaching, learning, reading and writing.